Examining Changes in Stem Taper and Volume Growth with Two-Date 3D Point Clouds - Ville Luoma; Ninni Saarinen; Ville Kankare; Topi Tanhuanpää; Harri Kaartinen; Antero Kukko; Markus Holopainen; Juha Hyyppä; Mikko Vastaranta (MDPI, 2022)
Exact knowledge over tree growth is valuable information for decision makers when considering the purposes of sustainable forest management and planning or optimizing the use of timber, for example. Terrestrial laser scanning (TLS) can be used for measuring tree and forest attributes in very high detail. The study aims at characterizing changes in individual tree attributes (e.g., stem volume growth and taper) during a nine year-long study period in boreal forest conditions. TLS-based three-dimensional (3D) point cloud data were used for identifying and quantifying these changes. The results showed that observing changes in stem volume was possible from TLS point cloud data collected at two different time points. The average volume growth of sample trees was 0.226 m(3) during the study period, and the mean relative change in stem volume was 65.0%. In addition, the results of a pairwise Student's t-test gave strong support (p-value 0.0001) that the used method was able to detect tree growth within the nine-year period between 2008-2017. The findings of this study allow the further development of enhanced methods for TLS-based single tree and forest growth modeling and estimation, which can thus improve the accuracy of forest inventories and offer better tools for future decision-making processes.